1992
DOI: 10.1017/s0890037x00034965
|View full text |Cite
|
Sign up to set email alerts
|

Reduced and Standard Herbicide Rates for Grass Control in Rice (Oryza sativa)

Abstract: Field research was conducted in 1988 and 1989 to compare effects of clethodim, fenoxaprop, haloxyfop, and sethoxydim each applied singly and sequentially at full (1X) and reduced (0.5X) rates on barnyardgrass, bearded sprangletop, and rice. A tank-mixture of propanil plus thiobencarb (2.2 + 2.2 kg ha–1) applied sequentially was included as a standard treatment. Control of barnyardgrass and bearded sprangletop was equal to that of the standard treatment both years with 1X rates of clethodim and fenoxaprop, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

1994
1994
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
4
0
3
Order By: Relevance
“…Rice injury has been documented with acetyl-CoA carboxylase (ACCase)-inhibiting herbicides (Baltazar and Smith 1994;Carey et al 1992;Griffin and Baker 1990;Stauber et al 1991). Research has also shown a differential tolerance and control among grass species for ACCase-inhibiting herbicides (Catanzaro et al 1993;Jordan et al 1997;Krausz et al 1993;Peters et al 1989;Street and Snipes 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Rice injury has been documented with acetyl-CoA carboxylase (ACCase)-inhibiting herbicides (Baltazar and Smith 1994;Carey et al 1992;Griffin and Baker 1990;Stauber et al 1991). Research has also shown a differential tolerance and control among grass species for ACCase-inhibiting herbicides (Catanzaro et al 1993;Jordan et al 1997;Krausz et al 1993;Peters et al 1989;Street and Snipes 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Embora investigando basicamente a ação de herbicidas sobre espécies daninhas dicotiledôneas, diversos autores (Mengarda & fleck, 1989;DeFelice et al, 1989;Steckel et al, 1990;Devlin et al, 1991;Carey et al, 1992;Klingaman et al, 1992) enfatizam que o uso de doses reduzidas de herbicidas de pós-emergência deve ocor rer cedo e sobre ervas de pequeno tamanho e em crescimento ativo, a fim de obter-se controle satisfatório. Além disso, a prática de doses reduzidas deve ocorrer sob condições ambientes favoráveis (Barrentine, 1989;DeFelice et al, 1989;Griffin et al, 1992Devlin et al, 1991.…”
Section: Resultsunclassified
“…Do mesmo modo como foi verificado por Prostko & Meade (1993), os resultados aqui relatados comprovaram também que os tratamentos usando metade das doses usuais não foram tão eficientes quanto doses plenas ou aplicações seqüenciais de doses correspondentes a apenas 25% das recomendadas. Carey et al (1992) obtiveram também controle satisfatório de capim-arroz em estádio inicial com uso N.G. Fleck de doses reduzidas em aplicações seqüenciais dos herbicidas graminicidas clethodim e fenoxaprop.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Cyhalofop has been reported to control barnyardgrass at least 88% when applied early POST (EPOST) as well as late POST (LPOST) at 200 g ai/ha (Ntanos et al 2000). Fenoxaprop applied at 170 g ai/ha has been reported to control 5 to 12-cm barnyardgrass at least 83% (Carey et al 1992).…”
mentioning
confidence: 99%